Relationship between GDP growth and deforestation in the Central American and Caribbean countries with further analysis on the major GDP earning industries among these countries and their contribution to deforestation - CHANG, Chia-Wei (KDI School, 2017)
Latin America and the Caribbean experiences most serious deforestation trend in the world. There is a total decrease of 970,000 square kilometers of forest area between 1990 and 2015 in the region, which translates to 10% loss in the original forest coverage. Conventionally, economists had based their study on the entire Latin America. However, this research paper will focus only on Central America and the Caribbean for that they demonstrate distinctive features that are different form the South American countries. The research attempts to identify how economic development can affect the forest coverage in Central American and Caribbean countries. It further argues that economic development will cause higher burden on the supply of natural resources and results in the decline of forest coverage. The econometrics model evaluates the contribution to deforestation from the major GDP earner industries, such as tourism and agriculture. It also considers other development factors like forest burned, population growth and urbanization into the model. Finally, this paper provides results that can lead to feasible policy recommendations that can assist the region in conserving its natural resources for future growth and developments.
Thesis(Master) --KDI School:Master of Public Policy,2017